System Demonstration of Nanosecond Wavelength Switching with Burst-mode PAM4 Transceiver - Shi, Kai; Lange, Sophie; Haller, Istvan; Cletheroe, Daniel; Behrendt, Raphael; Thomsen, Benn; Karinou, Fotini; Jozwik, Krzysztof; Costa, Paolo; Ballani, Hitesh (The 45th European Conference on Optical Communication (ECOC Post-deadline Paper), 2019)
We demonstrate a wavelength switching PIC whose switching time (0.912 ns) is independent of the tuning range, and an optical switching system (50Gbps PAM4) using the PIC and fast burst-mode channel equalization, achieving 3.84 ns switching latency.